Morphology of threespine stickleback (Gasterosteus aculeatus) in postglacial ponds, SE Iceland - Pace, Audrey, 1992- (2016)
The assessment of contemporary differences in morphology can provide important insight into the development of adaptation as it occurs. Fifteen populations of threespine stickleback were examined, that populate a trail of ponds in Breiðamerkursandur, Southeast Iceland. The ponds have been revealed in time by the retreating glacier Breiðamerkurjökull. Applying geometric morphometrics showed that all populations differed in body shape and that stickleback populations from ponds close in age were also more similar in morphology. In general this was more clear for populations in the old and in the young ponds. Populations in middle-aged ponds were more difficult to classify and to set into context. Within the pattern there were some relations that stood out, e.g. morphological similarities between populations in distant ponds (as BMS 01 and 10) o Prof. Bjarni K. Kristjánsson r very different morphology in populations of ponds that are very close in time and space (as BMS 01 and 02). These observations emphasise the impact of the various forces that affect polymorphism and call for further investigation of the stickleback populations in this area. Deeper morphological investigations, coupled with the estimation of several factors that influence adaptive radiation (prey assembly, predator pressure, genetic constraints of the stickleback, parasite infections etc.) will provide careful insight of how threespine stickleback evolve in the novel freshwater habitats of Iceland.